KARAKTERISTIK SIFAT FISIK TANAH ULTISOL BERDASARKAN TINGKAT KEMIRINGAN LERENG - Eko Dedi Septiaji; John Bimasri; Zaini Amin (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Ultisol soil has slow permeability and low aggregate stability, so it has low water holding capacity and is sensitive to erosion. The research was carried out from January to February 2024, in the Kebon Kito Agrotourism area at coordinates 3O19'20.52"S and 102O 55'25.92"E, which is in South Lubuklinggau I District, Lubuklinggau City, South Sumatra Province at an altitude of 105 meters above sea level using survey methods. The parameters observed in this research were bulk density, water content, pore space and soil pH at each slope, namely 25%, 30% and 35%. Data from field and laboratory research are processed using mathematical methods using formulas. The research results show that land with a small slope has a low bulk density (0.84 g/cm3), and has high water content, pore space and pH of 66%, 28.32% and 6.7 respectively. compared to land that has a greater slope. The conclusion of this research is that the steeper the slope on a land surface will cause an increase in unit weight and reduce the water content, pore space and acidity (pH) of the soil.